Making of Nanopore NaA Zeolite Membranes for Saline Wastewater Treatment - Kazemimoghadam, Mansoor (ASEAN Journal of Chemical Engineering, 2016)
Zeolite membranes have been studied extensively for more than fifteen years, mainly focusing on gas separation and liquid pervaporation processes. Recently, molecular dynamic simulation has shown that zeolite membranes are theoretically suitable for ion removal from aqueous solutions. This work proposes to use zeolite membranes for desalination of saline recycled wastewater for the possibility of avoiding the costly treatment needed for saline wastewater by Conventional approaches. NaA zeolite membrane indicates that it may be possible to simultaneously separate ions and dissolved organic compounds from water by pervaporation (PV) processes. NaA zeolite membranes composed of a continuous intergrowth of NaA zeolite crystals have been prepared hydro thermally on the surface of porous tubular supports. In this research, synthesis of zeolite NaA membrane was investigated. SEM and XRD analysis have been used to confirm zeolite NaA membrane formation. Membrane performance has been evaluated using an experimental pervaporation setup. Effects of operation condition (temperature, rate and pressure) on the membrane structure and performance have been investigated for NaA zeolite membranes grown onto seeded mullite supports.